Дослідження електрофізичних характеристик високовольтної обробки газоподібних вуглеводнів для отримання вуглецевих наноматеріалів - Богуславський, Леонід Зиновійович; Вінниченко, Дмитро Валерійович; Назарова, Наталя Станіславівна; Адамчук, Юрій Олегович; Чущак, Сергій Володимирович (НТУ "ХПІ", 2016)
Проведено дослідження електрофізичних характеристик режиму продуктивного синтезу нановуглецю. Визначено типові форми динамічних вольт-амперних характеристик, при яких здійснюється синтез вуглецевих наноматеріалів, та їх залежність від потужності в каналі розряду і довжини міжелектродного проміжку. Визначено функціонали, які характеризують форму розрядних імпульсів. На основі їх аналізу визначено найбільш інформативну характеристику для моніторингу довжини міжелектродного проміжку.

The study of the electrophysical characteristics of the discharge treatment of gaseous hydrocarbons was performed. The electrophysical features of the plasma channel formation in the carbonaceous gas (propane – butane mix) were set. The shapes of the currentvoltage characteristics, typical for the productive synthesis of the carbon nanomaterials were identified and their dependencies on the power in the discharge channel and the length of the electrode gap were obtained. The voltage levels, which guarantee the breakdown, and the voltage on the discharge channel, typical for the productive synthesis mode, were obtained experimentally. It was shown that if the change the electrode gap’s length occurs, the shape of the current and voltage pulses greatly varies. It complicates the analysis of the relations between the process parameters and the electrical characteristics. The functionals, which characterize the shape of the discharge pulses, were identified. Based on these functionals dependencies analysis, it was determined that the output power of the discharge channel is the most informative feature for the monitoring of the length of the electrode gap.
Investigation of high-voltage electro-physical characteristics of the handling of gaseous hydrocarbons to produce carbon nanomaterials
Keywords: синтез нановуглецю; вуглецеві наноматеріали; ВНМ; вольтамперні характеристики; ВАХ; carbon nanomaterials